Advancing the sensitivity of integrated epoxy-based Bragg grating refractometry by high-index nanolayers - Hessler, Steffen; Knopf, Stefan; Rommel, Mathias; Girschikofsky, Maiko; Schmauß, Bernhard; Hellmann, Ralf (Optics Letters, 2020)
In this Letter, we report on significantly improved surrounding RI sensitivity of epoxy polymer waveguide Bragg grating sensors. Uniform Bragg gratings were generated inside flat rectangular epoxy waveguides near the cutoff regime using standard phase mask excimer laser writing. Thickness controlled nanolayers of high-index titanium dioxide were deposited homogeneously on the waveguide sensor's surface area by repeated reactive sputter processing. Maximum Bragg wavelength shifts as high as 74.22 nm, as well as maximum sensitivities around 523 nm/RI unit corresponding to a minimum RI resolution of 1.9. 10(-6), could be obtained by employing a similar to 75 nm thick titanium dioxide coating. (C) 2020 Optical Society of America
CRIS-Team WoS Importer:2020-10-30